2019
DOI: 10.1016/j.neuropsychologia.2017.09.037
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of individuation and categorization of other-species faces in infancy

Abstract: The goal of this study was to investigate 9-month-old infants' ability to individuate and categorize other-species faces at the subordinate level. We were also interested in examining the effects of initial exposure conditions on infant categorization and individuation processes. Infants were either familiarized with a single monkey face in an individuation procedure or familiarized with multiple exemplars of monkey faces from the same species in a categorization procedure. Event-related potentials were record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…Research from our lab ( Dixon et al, 2017 ), has shown that although infants demonstrate poor performance at individuating monkey faces based on perceptual narrowing, they do seem to be efficient at categorizing other-species faces at 9 months of age. In addition to analyzing face processing components, we analyzed the Negative central (Nc) ERP component associated with infant attentional engagement ( Courchesne et al, 1981 ; de Haan and Nelson, 1997 , 1999 , Reynolds and Richards, 2005 ; Reynolds et al, 2010 ; Reynolds, 2015 ; Reynolds and Romano, 2016 ).…”
Section: Neural Correlates Of Infant Face Processingmentioning
confidence: 95%
See 1 more Smart Citation
“…Research from our lab ( Dixon et al, 2017 ), has shown that although infants demonstrate poor performance at individuating monkey faces based on perceptual narrowing, they do seem to be efficient at categorizing other-species faces at 9 months of age. In addition to analyzing face processing components, we analyzed the Negative central (Nc) ERP component associated with infant attentional engagement ( Courchesne et al, 1981 ; de Haan and Nelson, 1997 , 1999 , Reynolds and Richards, 2005 ; Reynolds et al, 2010 ; Reynolds, 2015 ; Reynolds and Romano, 2016 ).…”
Section: Neural Correlates Of Infant Face Processingmentioning
confidence: 95%
“…The shaded rectangle indicates the time window for the analysis of Nc. Time following stimulus onset is shown on the X -axis, and change in amplitude of the ERP (in microvolts) is shown on the Y -axis (Figure adapted from Dixon et al, 2017 ).…”
Section: Neural Correlates Of Infant Face Processingmentioning
confidence: 99%
“…However, the effects of certain stimulus manipulations (emotions and spatial frequency) were not stable across measurement time points, calling into question whether differential responses can reliably be seen as indicative of individual developmental trajectories. Dixon et al (2017) focus on the effects of exposure to other-species faces on categorization and individuation in 9-month-olds' ERP responses. Whereas exposure to multiple exemplars facilitated infant categorization of monkey faces on the subordinate level, familiarization to an individual monkey face did not affect infant categorization or individuation of monkey faces, speaking to the specific effects of exposure to multiple exemplars of an unfamiliar face category on infant face perception.…”
mentioning
confidence: 99%